Molecular characterization of the tetratricopeptide repeat-mediated interactions of murine stress-inducible protein 1 with major heat shock proteins - Odunuga, Odutayo Odutola (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
Murine stress-inducible protein 1 (mSTI1) is a co-chaperone that is homologous with the human heat shock protein 70 (Hsp70)/heat shock protein 90 (Hsp90)-organizing protein (Hop). The two proteins are homologues of the highly conserved stress-inducible protein 1 (STI1) family of co-chaperones. The STI1 proteins interact directly and simultaneously at some stage, with Hsp70 and Hsp90 in the formation of the hetero-multi-chaperone complexes that facilitate the folding of signal transducing kinases and functional maturation of steroid hormone receptors. The interactions of mSTI1 with both Hsp70 and Hsp90 is mediated by a versatile structural protein-protein interaction motif, the tetratricopeptide repeat (TPR). The TPR motif is a degenerate 34-amino acid sequence a-helical structural motif found in a significant number of functionally unrelated proteins. This study was aimed at characterizing the structural and functional determinants in the TPR domains of mSTI1 responsible for binding to and discriminating between Hsp70 and Hsp90. Guided by data from Hop's crystal structures and amino acid sequence alignment analyses, various biochemical techniques were used to both qualitatively and quantitatively characterize the contacts necessary for the N-terminal TPR domain (TPR1) of mSTI1 to bind to the C-terminal EEVD motif of heat shock cognate protein 70 (Hsc70) and to discriminate between Hsc70 and Hsp90. Substitutions in the first TPR motif of Lysâ ¸ or AsnÂ¹Â² did not affect binding of mSTI1 to Hsc70, while double substitution of these residues abrogated binding. A substitution in the second TPR motif of Asnâ ´Â³ lowered but did not abrogate binding. Similarly, a deletion in the second TPR motif coupled with a substitution of Lysâ ¸ or AsnÂ¹Â² reduced but did not abrogate binding. Steady state fluorescence and circular dichroism spectroscopies revealed that the double substitution of Lysâ ¸ and AsnÂ¹Â² resulted in perturbations of inter-domain interactions in mSTl1. Together these results suggest that mSTI1-Hsc70 interaction requires a network of electrostatic interactions not only between charged residues in the TPR1 domain of mSTI1 and the EEVD motif of Hsc70, but also outside the TPR1 domain. It is proposed that the electrostatic interactions in the first TPR motif collectively made by Lysâ ¸ and AsnÂ¹Â² define part of the minimum interactions required for successful mSTI1-Hsc70 interaction. In the first central TPR domain (TPR1A), single substitution of LysÂ³Â°Â¹ was sufficient to abrogate the mSTI1-Hsp90 interaction. Using a truncated derivative of mSTI1 incapable of binding to Hsp90, residues predicted by crystallographic data to determine Hsp70 binding specificity were substituted in the TPR1 domain. The modified protein had reduced binding to Hsc70, but showed significant binding capacity for Hsp90. In contrast, topologically equivalent substitutions on a truncated derivative of mSTI1 incapable of binding to Hsc70 did not confer Hsc70 specificity on the TPR2A domain. These data suggest that binding of Hsc70 to the TPR1 domain is more specific than binding of Hsp90 to the TPR2A domain. In addition, residues C-terminal of helix A in the second TPR motif of mSTI1 were shown to be important in determining specific binding to Hsc70. Binding assays using surface plasmon resonance spectroscopy showed that the affinities of binding of mSTI1 to Hsc70 and Hsp90 were 2 Î¼M and 1.5 Î¼M respectively. Preliminary in vivo studies revealed differences in the dynamics of binding of endogenous and exogenous recombinant mSTI1 with Hsc70 and Hsp90. The outcome of this study poses serious implications for the mechanisms of mSTI1 interactions with Hsc70 and Hsp90 in the cell.
Keywords: Plants -- Effect of stress on; Proteins -- Purification; Electrophoresis; Heat shock proteins